Childhood abuse history and attention bias in adults. (7th July 2020) - Letkiewicz, Allison M.; Silton, Rebecca L.; Mimnaugh, Katherine J.; Miller, Gregory A.; Heller, Wendy; Fisher, Joscelyn; Sass, Sarah M.
Abstract: Attention biases toward unpleasant information are evident among children and adults with a history of abuse and have been identified as a potential pathway through which abused children develop psychopathology. Identifying whether a history of childhood abuse affects the time course of attention biases in adults is critical, as this may provide intervention targets. The present study examined the time course of attention bias during an emotion‐word Stroop task using event‐related potentials (ERPs) in a sample of adults with a range of child abuse histories using a categorical approach (comparing adults with or without a history of moderate‐to‐severe childhood abuse) and a dimensional approach (analyzing the range from no abuse to severe abuse in a continuous manner). Although behavioral performance did not vary as a function of abuse history, adults with a history of moderate‐to‐severe childhood abuse showed ERP evidence of early reduced processing of emotional stimuli (smaller N200) and later reduced processing of emotional and nonemotional stimuli (smaller P300), followed by later increased processing of unpleasant stimuli (larger slow wave [SW]). Results suggest that early disengagement from emotional stimuli may help individuals with moderate‐to‐severe abuse histories to achieve normal behavioral performance on the emotion‐word Stroop task. Additionally, regardless of analytic approach, adults with elevated levels of childhood abuse exhibited prolonged engagement (larger SW) specifically with unpleasant stimuli. Present results demonstrate attention bias patterns in adults with a history of childhood abuse and clarify the time course of attention bias. Results are discussed in the context of potential treatment implications. Abstract : The present study evaluated the impact of a history of childhood abuse on the time course of attentional processing of emotional information in adults using ERPs. Although the effect of abuse on attention to emotional information has been examined extensively in children, it has been understudied in adults. The present study identified that adults with an abuse history showed earlier disengagement with emotional information followed by later prolonged engagement with unpleasant information. This is a pattern of processing that differs from children with a history of abuse. Results highlight the important potential avenues of intervention.